PENANAMAN NILAI RELIGIUS MELALUI PROGRAM INFAQ - SUSANTI, AGUS; RAHMATIKA, ZAHRA; ISTIANA, AIS; ARAFAH, ABDUL LATIEF ARUNG (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
The acceleration of globalization has led to the emergence of traits of wanting to reveal one's identity, such as wealth and arrogance. This also happens in educational institutions, especially in schools, so it is necessary to instill religious values by the school, one of which is through infaq. This research aims to analyze the instillation of religious values and determine the supporting and inhibiting factors in instilling religious values through student donations at MA Bandar Lampung. This research uses descriptive qualitative methods, and uses source triangulation and technical triangulation in data collection. The results of the research show that in MA Bandar Lampung implements infaq using two methods: through the smart Islamic boarding school application for infaq and cash payments. The fees collected every week are 150-300 thousand rupiah and are used for social activities such as natural disasters and bereavement at school. In its implementation, the cultivation of religious values through infaq at MA Bandar Lampung is supported by students' explanations regarding infaq from the moment they enter school and continuous habituation is carried out by the school. Infaq planting is also supported by several factors, namely: reminders from the infaq committee, support from parents with financial adequacy and high awareness. The factor that hinders the process of instilling religious values through infaq is the lack of pocket money for some students so that the amount of infaq results is small. ABSTRAKPercepatan globalisasi menyebabkan munculnya sifat ingin memunculkan jati diri seperti harta dan kesombongan. Inipun terjadi di lembaga pendidikan khususnya di sekolah sehingga diperlukan penanaman nilai religius oleh pihak sekolah salah satunya melalui infaq. Penelitian ini bertujuan untuk menganalisa penanaman nilai religius serta mengetahui faktor pendukung dan penghambat dalam penanaman nilai religius melalui infaq siswa di MA Bandar Lampung. Penelitian ini menggunakan metode kualitatif deskriptif, dan menggunakan triangulasi sumber dan triangulasi teknik dalam pengumpulan datanya. Hasil penelitian menunjukkan bahwa di MA Bandar Lampung menerapkan infaq menggunakan dua cara : melalui aplikasi smart pesantren untuk berinfaq dan pembayaran cash. Biaya yang terkumpul setiap minggunya yakni 150-300 ribu rupiah dan digunakan untuk kegiatan sosial seperti bencana alam, dan duka di sekolah. Dalam pelaksanaannya penanaman nilai religius melalui infaq di MA Bandar Lampung didukung oleh penjelasan siswa mengenai infaq sejak awal masuk ke sekolah dan dilakukan pembiasaan terus menerus oleh pihak sekolah. Penanaman infaq juga didukung oleh beberapa faktor yaitu : adanya reminder dari panitia infaq, adanya dukungan dari orang tua dengan kecukupan finansial serta kesadaran tinggi. Adapun faktor yang menghambat proses penanaman nilai religius melalui infaq yaitu kurangnya uang jajan pada sebagian siswa sehingga jumlah hasil infaq kecil.